2019
DOI: 10.3390/fishes4020027
|View full text |Cite
|
Sign up to set email alerts
|

A Blend of F Prostaglandins Functions as an Attractive Sex Pheromone in Silver Carp

Abstract: A series of laboratory experiments tested the hypothesis that the Silver Carp (Hypophthalmichthys molitrix), an invasive river carp from China, employs a prostaglandin F2α-derived sex pheromone that is attractive and species-specific. Using electro-olfactogram recording (EOG), we found that the olfactory system of this species is acutely sensitive to three F-series prostaglandins (PGFs) at picomolar concentrations and that this sensitivity is enhanced when juveniles are masculinized using androgens, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…S3 A ). As carp have been shown to produce a blend of PGF 2α metabolites ( 52 ), we also tested for a male preference for a mixture of PGF 2α plus five known metabolites from mammals (15K-PGF 2α , PGFM, 13,14-DH PGF 2α , 19(R)-hydroxy PGF 2α , and 20-hydroxy PGF 2α ). However, our data showed that neither PGF 2α nor a mixture of the five known PGF 2α metabolites is sufficient to attract male cichlids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 A ). As carp have been shown to produce a blend of PGF 2α metabolites ( 52 ), we also tested for a male preference for a mixture of PGF 2α plus five known metabolites from mammals (15K-PGF 2α , PGFM, 13,14-DH PGF 2α , 19(R)-hydroxy PGF 2α , and 20-hydroxy PGF 2α ). However, our data showed that neither PGF 2α nor a mixture of the five known PGF 2α metabolites is sufficient to attract male cichlids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we do not believe that a failure of males to seek synthetic PGF 2α metabolites results from insufficient stimulation. In some species, the ratio of the metabolites produced has been suggested to be important for attraction ( 52 , 63 ). We delivered chemicals in approximately equimolar ratios, so we cannot exclude a model in which cichlids compare concentrations of individual compounds within a blend.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there was a positive association between eDNA copy numbers and carp presence (total fish detections), suggesting eDNA might also be used for the quantification of aggregating carps. Although the PGF2α sex pheromone has yet to be tested with silver carp, it is highly likely that it could also be used on this invasive carp as it has proven to be highly attractive to them in small-scale laboratory tests [14,21]. Of course, large-scale tests of both of these stimuli must now be conducted in flowing river waters.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, we tested a solution of 10 −9 M PGF2α (Cayman Chemical Co., Ann Arbor, MI, USA) [14,18]. For the latter, we created the pheromone complex following established protocols, which entailed implanting carp with PGF2α [18,19,21] and collecting holding water (Supplemental Data S1). The concentration of PGF2α in the mixture was determined to be 10 −9 M by mass spectrometry [11].…”
Section: Experiments 2: Pheromone and Male Common Carpmentioning
confidence: 99%
“…The invasion of bighead and silver carp into North American waters is of concern due to their negative impact on ecosystems by directly competing with native species for resources; this competition can cause a reduction in native fish diversity [2]. A variety of research has been conducted on food additives and compounds such as food cues (e.g., amino acids), pheromones, and alarm-eliciting compounds that could be used to attract and aggregate invasive carp for easier removal by managers [13][14][15]. This research is intended to inform the management of invasive carp control activities by the United States Fish and Wildlife Service, the Army Corps of Engineers, and multiple state agencies.…”
Section: Introductionmentioning
confidence: 99%